Pengaruh Asimetri Informasi, Female Director, Board Independence Terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Amelia Dwi Wirantika; Dieanya Ramadhanty Surya Pradita; Sany Sany (Business Accounting Review, 2021)
This study aims to obtain evidence regarding the effect of information asymmetry, female director, and board independence on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Earnings management, information asymmetry, female director and board independence are measured by a ratio scale. The control variables used are leverage and firm size. The sample used is 60 manufacturing sector companies that have been listed on the IDX in the 2016-2020 period. This research uses GRETL software in data processing using multiple linear regression method. Based on the results of the study, it shows that information asymmetry, female director and board independence have no effect on earnings management.